Penerapan Teknologi Tepat Guna dalam Menunjang Ketahanan Pangan Keluarga melalui Budidaya Jamur Tiram di Desa Pecuk, Kabupaten Demak: The Application of Appropriate Technology to Support Household Food Security through Oyster Mushroom Cultivation in Pecuk Village, Demak Regency - Arini, Nindya; Anwar, Khairul; Anwar, syaiful; Arumsari, Nurul Rizka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Pecuk Village is one of the villages in Mijen District, Demak Regency, Central Java Province. Pecuk Village covers an area of 256.019 hectares with a population of 2,597 people. Almost half of the residents of Pecuk Village fall into the category of pre-prosperous families, amounting to 43.69%. The village government continues to strive to improve the welfare of its residents, one of which is through food security programs such as mushroom cultivation. The purpose of this activity is to improve the partners' understanding and skills in oyster mushroom cultivation, as well as to enhance their organizational management knowledge regarding mushroom business groups at the village level. The community service method involved lectures/briefings, discussions and Q&A sessions, practical sessions, evaluation, and assistance. The activity was carried out using the planned methods and stages. The socialization and practical training on how to prepare growing media for oyster mushrooms, along with the use of a baglog press tool, increased the residents' enthusiasm for mushroom cultivation. The high level of community participation in this program indicates that the activity was well received. The approach taken helped increase participants' motivation to carry out proper oyster mushroom cultivation. In addition to receiving equipment support, the community also gained technical knowledge on media preparation and maintenance, which contributes to the program's sustainability. As a result, this initiative is expected to serve as a positive first step in supporting household food security and improving the local economy.